Characteristics of mucoid Streptococcus pyogenes isolated from two patients with pneumonia in a local community. (2016) - Mori, Nobuaki; Hosoo, Sakiko; Oyamada, Yoshitaka; Sera, Yasushi; Yamada, Yasuhiro; Sugawara, Momoko; Higuchi, Akiko; Aoki, Yasuko; Takahashi, Takashi
Abstract: Streptococcus pyogenes (Group A Streptococcus, GAS) infections can develop into life-threatening disorders. However, the occurrence of some GAS pneumonia cases is relatively rare in a local community. We report here characteristics of mucoid GAS isolates obtained from the sputum of two patients with pneumonia in a local community. Although case-patients did not have contact with each other, case-patient 1′s child and case-patient 2′s grandchild attended the same kindergarten where a GAS pharyngitis epidemic had occurred. We conducted phenotypic and genotypic analyses with the GAS isolates from sputum of both patients, to examine (1) colony appearance between the isolates, (2) numerical profile based on API-20 Strep system, (3) similarity to the type strain using 16S rRNA sequencing, (4) emm type (subtype) and emm full-length sequence, (5) sequence type, (6) sic allele, (7) antimicrobial susceptibility result and the resistance determinant, (8) genome profile following a random amplified polymorphic DNA fragments, and (9) pattern of digested DNA fragments by pulse-field gel electrophoresis. These phenotypic and genotypic analyses revealed similar matching between the isolates from both cases. Our findings suggest that when clinicians examine adult patients having infection with the mucoid GAS, they should confirm whether anyone within the same household also developed the infection and need to investigate epidemic situations in local communities, including kindergartens and elementary schools.